Problems of future philologists' training in modern scientific discourse - Maryna Ikonnikova (Vasyl Stefanyk Precarpathian National University, 2017)
Philosophical, psychological-pedagogical and sociolinguistic projections of future philologists' professional training have been studied in the paper. It has been defined that they provide for creating optimal conditions for learning language, literature, translation, etc.; stimulating speech and mental activity of students; developing their critical thinking skills, linguistic personality, multiple intellect, the ability to model conceptual information; widening knowledge-based space taking into account individual styles and strategies for student learning. It has been indicated that within foreign scientific discourse scholars focus on the problem of training philologists of the integrated type that is possible provided the methodology is scientifically justified, based on the significant achievements of philosophy, psychology, pedagogy, linguodidactics, sociolinguistics and culturology, oriented toward European requirements to language education, positive foreign experience and national traditions. Key words: future philologists, professional training, philological education, philology, scientific discourse.